Technological innovations for enhancing spices productivity and doubling farmers income - Dinesh, R; Srinivasan, V; Praveena, R (Indian Horticulture, 2025)
Spices have significantly shaped India’s political and economic landscape through their flavour, preservative properties, and medicinal value. Formal spice research in India commenced in 1951 with the Spices Enquiry Committee, leading ICAR to oversee structured investigations. This paper traces the evolution of ICAR-IISR from its origins in the All India Coordinated Spices and Cashew Nut Improvement Project to its establishment as a regional CPCRI station in 1975, its elevation to NRC for Spices in 1986, and its transformation into ICAR-IISR in 1995. ICAR-IISR’s mandate encompasses germplasm conservation, development of highyielding,stressresistant spice varieties, integrated crop management, biotechnology use, and farmer-centric technology transfer.